Cellular Membranes, a Versatile Adaptive Composite Material - Lamparter, Lucas; Galic, Milos (Frontiers in Cell and Developmental Biology, 2020)
Cellular membranes belong to the most vital yet least understood biomaterials of live matter. For instance, its biomechanical requirements substantially vary across species and subcellular sites, raising the question how membranes manage to adjust to such dramatic changes. Central to its adaptability at the cell surface is the interplay between the plasma membrane and the adjacent cell cortex, forming an adaptive composite material that dynamically adjusts its mechanical properties. Using a hypothetical composite material, we identify core challenges, and discuss how cellular membranes solved these tasks. We further muse how pathological changes in material properties affect membrane mechanics and cell function, before closing with open questions and future challenges arising when studying cellular membranes.